Effects of whole-body vibration training on inflammatory markers and lipid profiles in adults: a systematic review and meta-analysis of randomized controlled trials - Pan, Yan; Luo, Ping; Pang, Junpeng (Frontiers in Immunology, 2025)
ObjectiveThe aim of this study was to synthesize existing randomized controlled trials (RCTs) to investigate the effects of whole-body vibration (WBV) training on inflammatory markers and lipid profiles in adults.MethodsIn this meta-analysis, we systematically searched four major electronic databases—PubMed, Web of Science, Cochrane, and Embase—from their inception until August 15, 2025, to ensure comprehensive coverage of the relevant literature. The primary outcome indicators analyzed in this study included interleukin-6 (IL-6), interleukin-8 (IL-8), tumor necrosis factor-alpha (TNF-α), high-sensitivity C-reactive protein (hs-CRP), triglycerides (TG), total cholesterol (TC), low-density lipoprotein (LDL), and high-density lipoprotein (HDL). We conducted data analysis using the Stata 17.0 software to perform a statistical analysis of the combined effect sizes for each indicator.ResultsA total of 11 RCTs were included, involving 409 participants. The results showed that WBV training significantly reduced TNF-α [weighted mean difference (WMD) = −0.80 pg/mL, 95% CI: −1.14 to −0.47, p < 0.001], hs-CRP (WMD = −0.68 mg/L, 95% CI: −0.94 to −0.43, p < 0.001), and TG [standardized mean difference (SMD) = −0.67, 95% CI: −1.15 to −0.19, p = 0.006] levels in adults. However, no significant effects were observed for IL-6 (WMD = −0.50 pg/mL, 95% CI: −2.08 to −1.08, p = 0.535), IL-8 (WMD = 0.30 pg/mL, 95% CI: −0.26 to 0.85, p = 0.296), TC (SMD = −0.28, 95% CI: −0.57 to 0.02, p = 0.067), LDL (SMD = −0.47, 95% CI: −0.98 to 0.03, p = 0.068), and HDL (SMD = 0.43, 95% CI: −0.17 to 1.03, p = 0.156).ConclusionThis study confirmed that WBV training can positively impact inflammatory markers (TNF-α and hs-CRP) and lipid profile (TG) in adults. These findings provide important evidence for health management and intervention strategies for chronic disease prevention in adults, further supporting WBV training as an effective exercise intervention strategy for promoting metabolic health.Systematic Review RegistrationPROSPERO (CRD420251124521) https://www.crd.york.ac.uk/prospero/CRD420251124521.